Al-Zn-Mg-Sc alloy and application
By optimizing the composition and manufacturing process of Al-Zn-Mg-Sc alloy, the problems of difficulty in forming wires and insufficient mechanical properties in arc additive manufacturing of Al-Zn-Mg-Sc alloys are solved, and high strength and high extension are achieved Aluminum alloy wire material is suitable for printing industrial components.
Patent Information
- Application Number
- CN202411300259.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing Al-Zn-Mg-based aluminum alloy wire materials have problems such as wire formation difficulties, insufficient strength and elongation in the arc additive manufacturing process, resulting in less application in industrial production.
By optimizing the alloy composition, reducing the Zn content, increasing the mass percentage of Mg, adding trace Cu, Ti and other elements, combining cold metal transition (CMT) arc additive manufacturing and arc swing printing process, controlling impurity elements such as Fe, Si, H, etc. content, T6 heat treatment is performed to improve the strength and elongation of the alloy.
A high-strength and high elongation Al-Zn-Mg-Sc alloy wire material has a tensile strength of ≥340MPa, a yield strength of ≥230MPa, and an elongation of ≥15%. The mechanical properties are further improved through heat treatment to tensile strength of ≥500MPa , the yield strength is ≥450MPa and the elongation is ≥10%, and it is suitable for printing industrial components with high strength and high elongation.
Smart Images

Figure CN119282483A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum alloy wire, in particular to an Al-Zn-Mg-Sc alloy and an application thereof. Background Art
[0002] Aluminum alloy wires such as Al-Cu, Al-Si, and Al-Mg have been successfully manufactured into qualified products through arc additive manufacturing and have been successfully used in aviation, aerospace, weapons and other fields, demonstrating the unique advantages of arc additive manufacturing technology in the manufacture of aluminum alloy components with high efficiency, low cost and the manufacture of large structural parts.
[0003] Al-Zn-Mg aluminum alloy is an aluminum alloy with Zn and Mg as the main elements. It is a heat-treatable aluminum alloy with good thermal deformation performance and a wide quenching range. Under appropriate heat treatment conditions, it can obtain high strength and good weldability. At present, there are few studies on arc additive manufacturing of Al-Zn-Mg aluminum alloy wires, and there are few reports on the successful application of products in industrial production.
[0004] The Chinese patent announcement number CN111471905A discloses an Al-Zn-Mg-Sc aluminum alloy wire for 3D printing and a preparation method thereof. The tensile strength of the 3D printed parts using the aluminum alloy wire is 470-520MPa, the yield strength is 370-410MPa, and the elongation is 9%-12%. The metal raw material includes the following chemical elements in mass percentage: Zn 6.5%-8.3%, Mg 2.5%-3%, Mn 0.3%-0.8%, Zr 0.05%-0.25%, Cu 0.3%-0.8%, Sc 0.1%-0.5%, Ti 0.03%-0.06%, impurities ≤0.3%, and the balance is Al.
[0005] The Chinese patent application with publication number CN116144993A discloses a 7 series aluminum alloy wire for arc additive manufacturing, a preparation method and an application thereof, wherein the aluminum alloy wire product printed by cold metal transition (CMT) has a horizontal tensile strength of ≥620MPa, a yield strength of ≥520MPa and an elongation of ≤6.2%. The aluminum alloy wire contains the following components and their mass percentages: Zn 6.0% to 10.0%, Mg 1.5% to 2.8%, Cu 1.0 to 2.2%, Zr 0.05% to 0.25%, Sc 0.1% to 0.45%, Ti 0.05% to 0.25%, Fe ≤ 0.15, Si ≤ 0.10%, and the balance is Al.
[0006] The aluminum alloy wires in the above two patents are difficult to be made into wires due to work hardening and precipitation strengthening during the production process, and it is difficult to obtain high-quality wires. Summary of the invention
[0007] The present invention aims to provide an Al-Zn-Mg-Sc alloy and application thereof, which is suitable for printing industrial components with high strength and high elongation.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] An Al-Zn-Mg-Sc alloy comprises the following alloying elements by mass percentage: Zr content 0.15-0.25%, Sc content 0.225-0.375%, Ti content ≤0.1%, Cu content ≤0.1%, Zn content 4.0-5.5%, Mn content 0.2-0.6%, Mg content 2.0-4.0%, Cr content 0.1-0.3%, Be content 0.0001-0.005%, and the balance is Al.
[0010] The invention reduces the Zn content, increases the mass percentage of Mg, improves the strength, reduces the welding crack tendency, and improves the corrosion resistance of the alloy.
[0011] In the composition design of the present invention, a trace amount of Cu element is added to improve the stress corrosion resistance and tensile strength, but reduce the weldability of the alloy, and the designed Cu content is ≤0.1%.
[0012] In the composition design of the present invention, a trace amount of Ti element is added, which can refine the cast structure of the alloy during the printing process and improve the weldability of the alloy. The Ti content is designed to be ≤0.1%.
[0013] Preferably, an Al-Zn-Mg-Sc alloy comprises the following alloying elements, measured by mass percentage: Zr content 0.15-0.25%, Sc content 0.25-0.35%, Ti content ≤0.1%, Cu content ≤0.1%, Zn content 4.0-5.5%, Mn content 0.2-0.5%, Mg content 2.2-4.0%, Cr content 0.1-0.3%, and Be content 0.0001-0.005%.
[0014] Further preferably, an Al-Zn-Mg-Sc alloy comprises the following alloying elements, by mass percentage: Cu 0.08%, Zn 5.4%, Mn 0.43%, Mg 2.8%, Zr 0.23%, Sc 0.35%, Ti 0.03%, Si 0.05%, Fe 0.08%, Cr 0.21%, Be 0.0005%, and the rest is Al.
[0015] According to the embodiments of the present invention, the present invention can be further optimized. The following is the technical solution formed after optimization:
[0016] In one preferred embodiment, Fe≤0.1%, Si content≤0.05%, individual impurity elements≤0.05%, and the total amount≤0.15%.
[0017] In the composition design of the present invention, Fe is a harmful element that reduces the corrosion resistance and mechanical properties of the alloy and easily forms coarse compounds with Mn and Al, so the Fe content is strictly controlled to be ≤0.1%.
[0018] In the composition design of the present invention, Si is a harmful element that reduces the strength and bending performance of the alloy and increases the tendency of welding cracks, so the Si content is strictly controlled to be ≤0.05%.
[0019] In one preferred embodiment, 7.5%≤w(Zn+Mg)≤9.5%, and w(Zn):w(Mg)≤2.5.
[0020] Wherein, w(Zn+Mg) is the sum of the mass contents of Zn and Mg.
[0021] In one preferred embodiment, w(Mn):w(Cr)=2. The two together improve the stress corrosion resistance of the alloy and reduce the tendency of stress corrosion.
[0022] In one preferred embodiment, w(Sc):w(Zr)=1.5, which can refine the grain structure, improve the weldability and recrystallization end temperature of the aluminum alloy, and improve the elongation of the aluminum alloy.
[0023] w(Mn), w(Cr), w(Sc), and w(Zr) refer to the mass percentages of Mn, Cr, Sc, and Zr, respectively.
[0024] In one preferred embodiment, the H content is ≤0.15mL / 100gAl. In the composition design of the present invention, the H content in the melt in the aluminum alloy casting process is strictly controlled. The H in the melt is easy to form pores, pinholes and looseness during the solidification process, and may also cause secondary pores, bubbles, etc. during the subsequent processing, which is not conducive to wire drawing and printing. Therefore, H is strictly controlled to be ≤0.15mL / 100gAl, and the lower the better.
[0025] Among them, H is the hydrogen element.
[0026] In one preferred embodiment, the grain size D90 is less than 30 μm.
[0027] The present invention discloses an application of the Al-Zn-Mg-Sc alloy in arc additive manufacturing. The Al-Zn-Mg-Sc alloy is used as a filling material for arc additive manufacturing. The printing process parameters adopted are: current 90-130A, voltage 9.4-12.5V, printing speed 450-620mm / min, protective gas flow rate 18-25L / min, and swing arc printing.
[0028] In one preferred embodiment, the protective gas is argon with a purity of 99.999%.
[0029] A comprehensive analysis of the reasons for the difficulty in filament formation in the Chinese patent application with publication number CN116144993A is that during the arc additive manufacturing process, the higher the content of Zn and Mg elements, the more serious the burn-in, and Zn is particularly sensitive to the tendency of thermal cracking, resulting in seriously low Z-direction mechanical properties of the printed body, very prominent directional differences, and extremely low elongation, which makes it impossible to carry out actual industrial applications.
[0030] Cu, Zn, and Mg are the main strengthening elements in Al-Zn-Mg-Sc aluminum alloy wire for arc additive manufacturing. The Cu element mainly improves the strength of the aluminum alloy by forming S (Al2 CuMg) phase and θ (Al2 Cu) phase. When the Cu content is too high, the crack resistance of the aluminum alloy decreases. When Zn and Mg coexist, η (MgZn2) and T (Al2Mg2Zn3) are formed. The solubility of η phase and T phase in aluminum changes dramatically with the rise and fall of temperature, and has a strong precipitation strengthening effect. The higher the Zn and Mg content, the higher the strength and hardness, but the plasticity, stress corrosion resistance and fracture toughness decrease. Mn, Sc, Zr, Ti, Be, and Cr are trace beneficial elements. Fe, Si, H, etc. are impurity elements.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention adopts Al, Zn and Mg as main materials, adds trace amounts of beneficial elements such as Cu, Mn, Sc, Zr, Ti, Be and Cr to the main materials, and strictly controls impurity elements such as Fe, Si and H. The 3D printing filaments with the above composition are used to print samples, and the mechanical properties of the printed body are as follows: tensile strength ≥340MPa, yield strength ≥230MPa, elongation 15%, directional variability ≤5%; the mechanical properties after T6 heat treatment are improved to: tensile strength ≥500MPa, yield strength ≥450MPa, elongation ≥10%, directional variability ≤5%.
[0033] The advantages of the material of the present invention over the existing Al-Zn-Mg alloy wire are: low Zn content, high Mg content, high trace elements and reasonable ratio, which are more conducive to the printing process, especially the Zn content is a key element restricting the elongation.
[0034] The present invention adopts cold metal transition (CMT) arc additive manufacturing to print Al-Zn-Mg-Sc wire. By optimizing the printing process parameters, especially swing arc printing, anisotropy can be effectively eliminated. At the same time, with the assistance of heat treatment system, qualified components with high strength and high elongation can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the aluminum alloy printed body prepared in Example 1.
[0036] Figure 2 This is the aluminum alloy printed body prepared in Example 2.
[0037] Figure 3 This is the metallographic structure diagram of the aluminum alloy printed body T6 prepared in Example 3.
[0038] Figure 4 This is the metallographic structure diagram of the aluminum alloy printed body T6 prepared in Example 4. DETAILED DESCRIPTION
[0039] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0040] Embodiment 1: The chemical composition (mass percentage) of the designed Al-Zn-Mg-Sc aluminum alloy wire is: Cu 0.08%, Zn 5.4%, Mn 0.43%, Mg 2.8%, Zr 0.23%, Sc 0.35%, Ti 0.03%, Si 0.05%, Fe 0.09%, Cr 0.21%, Be 0.0005%, and the rest is Al. The qualified wire is obtained through the following production process of continuous casting - continuous extrusion - drawing into wire.
[0041] The specific process parameters are as follows:
[0042] (1) Aluminum liquid smelting: add aluminum ingots, aluminum-manganese alloy, aluminum-titanium alloy, aluminum-chromium alloy, aluminum-copper alloy, aluminum-zirconium alloy, and aluminum-scandium alloy into the medium frequency furnace and heat and melt them. Then add zinc ingots, magnesium ingots, and aluminum-beryllium alloy and heat and melt them. The aluminum liquid temperature is 740-750℃. Mechanical stirring is performed for 30 minutes at a speed of 300r / min. The element composition is analyzed and adjusted before the furnace to obtain qualified aluminum liquid.
[0043] (2) Refining and degassing: The aluminum liquid is transferred to a refining furnace for refining and degassing. 99.999% Ar gas is filled into the aluminum liquid for refining and degassing. The Ar gas flow rate is 20L / min. The refining is performed for 25 minutes. After refining and degassing, the aluminum liquid is allowed to stand for temperature adjustment. The hydrogen content in the aluminum melt after treatment is ≤0.12ml / 100g.
[0044] (3) Online filtration: A two-stage filtration device is used to perform online degassing, deslagging and filtration on the aluminum melt; the removal rate of inclusions with a particle size greater than 1 μm in the aluminum melt is controlled to be greater than 90%.
[0045] (4) Continuous casting: The casting temperature ranges from 710°C to 720°C. The crystallization wheel has its own water cooling system. The cooling water temperature ranges from 15°C to 30°C. The aluminum liquid is cooled and solidified by the crystallization wheel. The casting speed is 100-120kg / h to obtain a φ9.5mm aluminum rod blank.
[0046] (5) Continuous extrusion: After the surface oxide scale of the aluminum rod is scraped off, it is cleaned and preheated, and then pressed into the wheel groove of the extrusion wheel by the compaction wheel. The speed of the extrusion wheel is 7 rpm to obtain a wire blank with a diameter of 2.7 mm;
[0047] (6) Intermediate annealing: heat to 320℃ for 2 hours, keep at 320℃ for 1.5 hours, cool to 270℃ for 2 hours, keep at 270℃ for 3.5 hours, and air cool after leaving the furnace.
[0048] (7) Drawing and scraping: The annealed wire billet is drawn to a nearly finished size of φ1.2 mm at a speed of 4-6 m / s, and then the surface scratches and fatigue layer are scraped off by two consecutive stripping passes at a speed of 3-5 m / s.
[0049] The Al-Zn-Mg-Sc aluminum alloy wire with the above composition was used for arc additive manufacturing by cold metal transfer (CMT) printing. The printing process parameters are as follows: current 90A, voltage 11.8V, printing speed 540mm / min, shielding gas (argon) flow rate 18L / min, swing arc printing. During cold metal transfer (CMT) printing, the welding gun swings horizontally along the forward direction at the same time, and the swing angle is 30 degrees. Introducing swing arc welding technology into arc additive manufacturing can effectively eliminate the anisotropy of the printed part. The obtained aluminum alloy printed body can be seen in Figure 1. Figure 1 .
[0050] According to the tensile test standard GB / T228.1-2021, the test mechanical properties data are shown in Table 1:
[0051] Table 1
[0052]
[0053] Example 2: The chemical composition (mass percentage) of the designed Al-Zn-Mg-Sc aluminum alloy wire is: Cu 0.08%, Zn 5.4%, Mn 0.43%, Mg 2.8%, Zr 0.23%, Sc 0.35%, Ti 0.03%, Si 0.05%, Fe 0.09%, Cr 0.21%, Be 0.0005%, and the rest is Al. Using the Al-Zn-Mg-Sc aluminum alloy wire with the above composition, arc additive manufacturing is carried out by cold metal transfer (CMT) printing. The printing process parameters are as follows: current 90A, voltage 11.8V, printing speed 540mm / min, shielding gas (argon) flow rate 18L / min, see Figure 2 .
[0054] According to the tensile test standard GB / T228.1-2021, the test mechanical properties data are shown in Table 2:
[0055] Table 2
[0056]
[0057] Example 3: The chemical composition (mass percentage) of the designed Al-Zn-Mg-Sc aluminum alloy wire is: Cu0.06%, Zn5.0%, Mn0.46%, Mg3.3%, Zr0.21%, Sc0.30%, Ti0.05%, Si0.05%, Fe0.08%, Cr0.22%, Be0.0008%, and the rest is Al. Using the Al-Zn-Mg-Sc aluminum alloy wire with the above composition, arc additive manufacturing is carried out by cold metal transfer (CMT) printing, and the printing process parameters are as follows: current 110A, voltage 12.5V, printing speed 540mm / min, shielding gas (argon) flow rate 18L / min, swing arc printing.
[0058] According to the tensile test standard GB / T228.1-2021, the test mechanical properties data are shown in Table 3, and the metallographic structure is shown in Table 3. Figure 3 As shown:
[0059] Table 3
[0060]
[0061] Comparative Example 1:
[0062] The aluminum alloy wire printing of Example 1 of patent CN111471905A was used, and arc additive manufacturing was performed using cold metal transition (CMT) printing method. The printing process parameters and heat treatment system were exactly the same as those of Example 3.
[0063] According to the tensile test standard GB / T228.1-2021, the test mechanical properties data are shown in Table 4, and the metallographic structure is shown in Table 4. Figure 4 As shown:
[0064] Table 4
[0065]
[0066]
[0067] In Example 1 of the Chinese patent application with publication number CN111471905A, the mass percentage of Zn in the aluminum alloy wire composition is 6.5%, while the mass percentages of Sc and Zr are only 0.1% and 0.05%. Zn can significantly improve the strength of the material, but is not conducive to improving the welding performance and the elongation. The content of Sc and Zr is low, and the elongation cannot be improved. Although the use of swing arc printing can eliminate the directionality, after the same T6 heat treatment, the amount of grain boundary precipitation phase is significantly more than that of Example 3, resulting in an elongation of only 6%, and a yield strength ratio of ≥91%, which affects the use of the material.
[0068] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the embodiments made by those skilled in the art fall within the scope defined by the claims attached to the present invention.
Claims
1. An Al-Zn-Mg-Sc alloy, comprising the following alloying elements by mass percentage: Zr content 0.15-0.25%, Sc content 0.225-0.375%, Ti content ≤0.1%, characterized in that: Cu content ≤ 0.1%, Zn content 4.0-5.5%, Mn content 0.2-0.6%, Mg content 2.0-4.0%, Cr content 0.1-0.3%, Be content 0.0001-0.005%, and the balance is Al.
2. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: Fe≤0.1%, Si content≤0.05%, individual impurity element≤0.05%, total amount≤0.15%.
3. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: 7.5%≤w(Zn+Mg)≤9.5%, and w(Zn):w(Mg)≤2.
5.
4. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: w(Mn):w(Cr)=2.
5. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: w(Sc):w(Zr)=1.
5.
6. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: H content ≤ 0.15mL / 100gAl.
7. The Al-Zn-Mg-Sc alloy according to claim 1, characterized in that: The grain size D90 is distributed in the range of 0 to 30 μm.
8. An application of Al-Zn-Mg-Sc alloy in arc additive manufacturing, characterized in that: The Al-Zn-Mg-Sc alloy described in any one of claims 1 to 7 is used as a filling material for arc additive manufacturing, and the printing process parameters used are: current 90-130A, voltage 9.4-12.5V, printing speed 450-620mm / min, protective gas flow rate 18-25L / min, and swing arc printing.
9. The use according to claim 8, characterized in that: The protective gas is argon gas with a purity of 99.999%.
Citation Information
Patent Citations
Al-Zn-Mg-Sc series aluminum alloy wire for 3D printing and preparation method thereof
CN111471905A
7-series aluminum alloy wire for electric arc additive manufacturing as well as preparation method and application of 7-series aluminum alloy wire
CN116144993A
Aluminum alloy solder wire for rapid trains and manufacturing method thereof
CN101722381A
High-intensity welding wire for aluminum-zinc-magnesium-scandium alloy and preparing method thereof
CN103273214A
Silicon-rich in-situ reinforced powder cored wire material for 7075 aluminum alloy electric arc additive material and preparation method
CN112775584A
Cited By
Cold metal transition electric arc additive manufacturing process matched with 5R59 aluminum-scandium welding wire
CN120662909A